Pendampingan Pembuatan Media Pembelajaran Menggunakan Canva Kepada Para Guru SMP - Jelimun, Maria Olga; Selamat, Ely Heldydiana; Anung, Matilda Saputri; Jumat, Helena Indriyani; Darma, Benedicto Cahya (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
. The fundamental problems in this Community Service activity are (1) the teacher's ability to utilize technology as a learning medium. (2) Teachers tend not to use technology in designing learning media. The method used in implementing PKM is the empowerment model. This activity aims to assist the teachers to design interactive technology based learning media. This model is implemented using the following steps: 1) Observations are carried out to obtain joint agreement regarding the mechanism for mentoring activities. 2) holding a workshop which aims to explain and provide general knowledge regarding learning media and the Canva application. 3) The pretest is carried out to obtain comparative scores before mentoring and after mentoring. 4) Assistance in creating learning media using Canva. 4) The post test was carried out to see the teacher's skills and achievements in creating learning media using Canva. The scores obtained in the two tests created were analyzed statistically using the JAPS application. The scores between the two tests are different from each other. The median value of the pre-test results received a score of 55.0 which is categorized as